Annual effects of different organic fertilisers in a baby leaf crops system under tunnel in Southern Italy - Morra, Luigi; Bilotto, Maurizio; Baiano, Salvatore; Saviello, Giovanni; Cerrato, Domenico (Italian Journal of Agronomy, 2015)
In a farm devoted to the production of fresh-cut leafy vegetables located in Eboli (Salerno), it was carried out a trial to compare the effects on crops and soil organic carbon (SOC) of biowaste compost, olive pomace compost, buffalo manure applied to soil in two doses (15 and 30 t ha−1 fresh weight). The amendments were tested in order to start in defining a feasible strategy for the recovery/maintenance of soils in degradation due to the organic matter depletion triggered by the intensive soil tillage and the lack of organic matter returned to soil. In the year following the soil amendment, it was studied the crop sequence: rocket-basil-rocket. Analysis of nitrates concentration in leaves of rocket was carried out on samples of all the treatments picked up in the two cycles of rocket. Along the year, we observed that the higher yields promoted in the first six months (May-September) from the dose 15 t ha−1, were obtained with the dose 30 t ha−1 in the successive six months (November-May). This was due, probably, to the larger stock of total N supplied with dose 30 and its release in time. Buffalo manure amendment showed a higher quickness than composts in the supplying mineral nitrogen to the first crops. On the other hand, nitrates in leaves of rocket exceeded, more frequently, the limits fixed in EU Regulation n. 1258/2011 in the plots amended with buffalo manure. Instead, the treatments with olive pomace compost showed to exceed rarely the EU limits. Under tunnel, the intensive management based on 4-5 crop cycles per year and as much soil tillage, appeared the first cause to explain the lack of significant variation in SOC of plots treated with organic improvers after one year from their distribution. This result let us to suppose the need to study some modifications of the standard farm management in order to reduce the number of soil tillage in a year and, as a consequence, the main stress causing the high carbon mineralisation rate in soil under tunnel.